Impaired awareness: Why people with multiple sclerosis continue using cannabis despite evidence to the contrary - Feinstein, Anthony; Meza, Cecilia; Stefan, Cristiana; Staines, William R. (Brain and behavior, 2021)
Background With widespread moves toward legalization of cannabis, increasing numbers of people with multiple sclerosis (pwMS) are using the drug. Emerging MS‐related data show that cannabis can cause or exacerbate cognitive dysfunction. Objective To understand why people with MS continue using cannabis despite adverse cognitive consequences. It was hypothesized that lack of awareness, a component of metacognition, could explain this decision, in part. Method Forty pwMS who smoked cannabis almost daily were assigned by odd–even case number selection to either a cannabis continuation (CC) or cannabis withdrawal (CW) group. Both groups were followed for 28 days. All participants completed, at baseline and day 28, the brief repeatable battery of neuropsychological tests (BRNB) in MS for measures of processing speed, memory and executive function; Modified fatigue impact scale (mFIS) for self‐report indices of cognitive functioning. Results No significant baseline differences between the groups on the BRNB and mFIS. At day 28, significant improvement within group was seen on all measures of the BRNB, but only in the CW group (p = .0001 for all indices). A repeat measure ANOVA did not find any significant group (CC vs. CW) × time (baseline and day 28) interactions for the self‐report cognitive measures on the mFIS. Cannabis abstainers did report less ability to function away from home. All 19 participants in the CW group reverted to using cannabis on study completion despite being informed individually of their cognitive improvement. Conclusions and relevance The inability of pwMS to accurately appraise their memory and executive function can help explain, in part, why they continue to smoke cannabis despite objective evidence of the deleterious cognitive side effects of this behavior.